Construction of a 2D Graphene‐Like MoS2/C3N4 Heterojunction with Enhanced Visible‐Light Photocatalytic Activity and Photoelectrochemical Activity. Issue 14 (25th February 2016) - Yan, Jia; Chen, Zhigang; Ji, Haiyan; Liu, Zheng; Wang, Xin; Xu, Yuanguo; She, Xiaojie; Huang, Liying; Xu, Li; Xu, Hui; Li, Huaming
Abstract: Invited for the cover of this issue is the group of Huaming Li and Hui Xu at the Jiangsu University. The image depicts GL‐MoS2 /C3 N4 as a kind of stable, non‐toxic, and highly efficient photocatalyst for the degradation of pollutants. Read the full text of the article at 10.1002/chem.201503660 . Abstract : " It shows that human beings possess the wisdom and power for solving environmental problems, and also for creating a beautiful world by our own hands ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 4764 ff. (DOI: 10.1002/chem.201503660 ).